Interest and motivation of Indonesian and Malay students in the implementation of sports injury therapeutic massage - Ali Satia Graha; Kamal Bin Talib; Rina Yuniana; Martono Martono; Krisnanda Dwi Apriyanto; Satya Perdana (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2022)
This study was to find out the impact of interest and motivation of Indonesian and Malay students on implementation of management of minor post-Sports injury therapeutic massage. It was a descriptive-qualitative and descriptive quantitative mixed study with survey method. Conducted in 2021 in the Faculty of Sports Science of Yogyakarta State University. Total participans 68 students involved 50 Indonesian students and 18 Malay students. Used linkert scale instrument with modified questionnaire of interest, motivation and implementation, r-count r-table (0.235) and alpha chronbach of 0.655. The results of the study showed that: the interest of the students in the management of the injury was very low (2 students or 3%), low (21 students or 31%), high (42 students or 60%), and very high (4 students or 6%); the motivation of the students in the management of the injury was very low (3 students or 4%), low (25 students or 37%), and high (36 students or 53%), and very high (4 students or 6%); impact of the implementation of the Sports injury management by the students was very low (3 students or 4%), low (34 students or 50%), high (23 students or 34%), and very high (8 students or 12%). Concluded that the interest and the motivation was influenced by intrinsic and extrinsic factors that could influence learning result, while the learning result could be found out in the implementation. It was necessary to organize hard skill learning using repetitive method consistent with stimulus-response theoretical perspective.